Game of protocols: Is QUIC ready for prime time streaming?. Issue 3 (17th February 2019) - Arisu, Sevket; Yildiz, Ertan; Begen, Ali C.
Summary: Quick User Datagram Protocol (UDP) Internet Connections (QUIC) is an experimental and low‐latency transport protocol proposed by Google, which is still being improved and specified in the Internet Engineering Task Force (IETF). The viewer's quality of experience (QoE) in HTTP adaptive streaming (HAS) applications may be improved with the help of QUIC's low‐latency, improved congestion control, and multiplexing features. We measured the streaming performance of QUIC on wireless and cellular networks in order to understand whether the problems that occur when running HTTP over TCP can be reduced by using HTTP over QUIC. The performance of QUIC was tested in the presence of network interface changes caused by the mobility of the viewer. We observed that QUIC resulted in quicker start of media streams, better streaming, and seeking experience, especially during the higher levels of congestion in the network and had a better performance than TCP when the viewer was mobile and switched between the wireless networks. Furthermore, we measured QUIC's performance in an emulated network that had a various amount of losses and delays to evaluate how QUIC's multiplexing feature would be beneficial for HAS applications. We compared the performance of HAS applications using multiplexing video streams with HTTP/1.1 over multiple TCP connections to HTTP/2 over one TCP connection and to QUIC over one UDP connection. To that effect, we observed that QUIC provided better performance than TCP on a network that had large delays. However, QUIC did not provide a significant improvement when the loss rate was large. Finally, we analyzed the performance of the congestion control mechanisms implemented by QUIC and TCP, and tested their ability to provide fairness among streaming clients. We found that QUIC always provided fairness among QUIC flows, but was not always fair to TCP. Abstract : Quick User Datagram Protocol (UDP) Internet Connections (QUIC) is a new transport protocol that provides low‐latency communication, improved congestion control, stream multiplexing capability, and rapid deployment. QUIC has begun its standardization process with a strong interest in the Internet Engineering Task Force (IETF) community and it is already widely deployed for most Google services. This article evaluates QUIC's media‐streaming performance on wireless and cellular networks, its performance by comparing different types of multiplexing schemes and its fairness to TCP under various network conditions.